Is There a Claim to Deserved Punishment?. Issue 3 (September 2014) - Alm, David
Abstract In this paper I defend the view that persons have a claim to deserved treatment, including many forms of punishment, against an objection resting on the principle that it is not possible to have a claim to harmful treatment. I do not challenge this principle, but argue, rather, that the harms wrongdoers typically deserve either (a) are not genuine harms at all (for reasons relevant to their being deserved) or (b) are not relevant to the content of these wrongdoers' claims.